On continuous extension to the boundary of a domain of the Cauchy-type integral with parameter-dependent density - Plaksa, S. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.54We establish sufficient conditions for the continuous extension of a Cauchy-type integral whose density depends on the parameter to a nonsmooth integration line.